2015
DOI: 10.1016/j.foodchem.2014.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Structure, morphology and functionality of acetylated and oxidised barley starches

Abstract: Acetylation and oxidation are chemical modifications which alter the properties of starch. The degree of modification of acetylated and oxidized starches is dependent on the catalyst and active chlorine concentrations, respectively. The objective of this study was to evaluate the effect of acetylation and oxidation on the structural, morphological, physical-chemical, thermal and pasting properties of barley starch. Barley starches were acetylated at different catalyst levels (11%, 17%, and 23% of NaOH solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
99
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(120 citation statements)
references
References 32 publications
14
99
0
7
Order By: Relevance
“…While comparing the starch films without the addition of cellulose fibers, it was observed that the acetylated starch film showed a lower percentage of residues at 200 and 400 °C (Table ), showing that this film had less thermal stability than the native starch film. This could be attributed to the depolymerization of the starch chains during acetylation . In addition, the presence of fibers in polymeric matrix increased the thermal stability of the starch films.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While comparing the starch films without the addition of cellulose fibers, it was observed that the acetylated starch film showed a lower percentage of residues at 200 and 400 °C (Table ), showing that this film had less thermal stability than the native starch film. This could be attributed to the depolymerization of the starch chains during acetylation . In addition, the presence of fibers in polymeric matrix increased the thermal stability of the starch films.…”
Section: Resultsmentioning
confidence: 99%
“…Research efforts in the area of polymeric materials have focused on the development of biodegradable materials obtained from renewable resources . Among these materials the starches that are the most abundant and the cheapest materials that come from renewable resources stand out.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The XRD pattern of the pure HPMC powder (seen from [25] ) presented two diffraction peaks at around 8.6 and 20.1 , and the pure MC powder showed two diffraction peaks at around 9.0 and 20.0 , respectively. Relative crystallinity of the oleogel samples calculated by Jade 6.0 were approximately 40% according to the methods reported by El Halal et al [36] and Park et al [37] Relative crystallinity was calculated by Equation (2): [34,35] The pattern of XG powder (seen from [25] ) presented a broad peak at around 20.0 .…”
Section: Xrd Analysismentioning
confidence: 99%
“…During the oxidation process, the hydroxyl groups present at C-1, C-2 and C-3 of the starch molecules are initially oxidised to carbonyl groups and then to carboxyl groups, which indicate the degree of oxidation. Parallel to this, there is the breaking of glycoside bonds with partial depolymerisation of starch [5].…”
Section: Introductionmentioning
confidence: 99%